Intransitivity, Ergatives and Middles - García de la Maza, Casilda (Estudios Ingleses de la Universidad Complutense, 2009)
The grammatical status of the English middle construction has been the object of much debate in the literature. Some have proposed accounts according to which middles turn out to be not very different from ergatives (Fagan 1988, 1992). Others defend that middles are derived very much in the same way as passive structures (Keyser and Roeper 1984, Hoekstra and Roberts 1993). Yet others have denied the very existence of the middle construction as a grammatical category (Condoravdi 1989, Lekakou 2002). Building on the Unaccusative Hypothesis and on a careful interpretation of the Universal Theta Assignment Hypothesis (UTAH) (Baker 1997), this paper attempts to demonstrate that middles constitute an independent class of intransitive sentences, distinct from ergatives, unergatives and passives both in argument configuration and derivation. A clearer and more symmetrical picture of the English intransitivity paradigm emerges as a result.